2022
DOI: 10.22306/al.v9i2.279
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Urban Freight Regulations Impact on the Transportation Cost

Abstract: The paper will investigate the impact of the vehicle carrying capacity to which the local tax is applied on forming the cost of delivery. The cost of 1 ton of freight under different tax scenarios is estimated in the paper: without tax 0, with fixed tax – 10% and with progressive tax from 0 to 75%. The greatest effect on reducing the vehicle's load capacity during urban deliveries showed a progressive tax. The developed regression model allows determining the cost of transportation of 1 ton of goods depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To reduce local emissions related to distribution, Ehrler, Schoder and Seidel [30] found that some e-grocery retailers had started using electric vehicles. In Ukraine, light commercial vehicles and intermediate light commercial vehicles have also been recommended for use in reducing emissions on roads [31]. This means that there exists a variety of approaches used to reduce emissions from delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce local emissions related to distribution, Ehrler, Schoder and Seidel [30] found that some e-grocery retailers had started using electric vehicles. In Ukraine, light commercial vehicles and intermediate light commercial vehicles have also been recommended for use in reducing emissions on roads [31]. This means that there exists a variety of approaches used to reduce emissions from delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%